2012
DOI: 10.4049/jimmunol.1200071
|View full text |Cite
|
Sign up to set email alerts
|

The Non-Ig Parts of the VpreB and λ5 Proteins of the Surrogate Light Chain Play Opposite Roles in the Surface Representation of the Precursor B Cell Receptor

Abstract: The VpreB and λ5 proteins, together with Igμ-H chains, form precursor BCRs (preBCRs). We established λ5−/−/VpreB1−/−/VpreB2−/− Abelson virus-transformed cell lines and reconstituted these cells with λ5 and VpreB in wild-type form or with a deleted non-Ig part. Whenever preBCRs had the non-Ig part of λ5 deleted, surface deposition was increased, whereas deletion of VpreB non-Ig part decreased it. The levels of phosphorylation of Syk, SLP65, or PLC-γ2, and of Ca2+ mobilization from intracellular stores, stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…This binding is likely to be modulated by the non-Ig parts of SLC, since pre-BCR surface deposition depends on these subunits (53). The non-Ig parts contain arginines, which in the case of the λ5-subunit of SLC have been shown to signal pre-B cells (54).…”
Section: Checkpoint 2: Recognition Of Autoantigens By Pre-bcrs?mentioning
confidence: 99%
“…This binding is likely to be modulated by the non-Ig parts of SLC, since pre-BCR surface deposition depends on these subunits (53). The non-Ig parts contain arginines, which in the case of the λ5-subunit of SLC have been shown to signal pre-B cells (54).…”
Section: Checkpoint 2: Recognition Of Autoantigens By Pre-bcrs?mentioning
confidence: 99%
“…One complex present on all c-kit positive pro-B cells consisted of λ5 and VpreB1 but not μHC. As these were pro-B cells, the complex was termed a pro-BCR, a receptor that in addition to SL chain consists of several molecules, of which only one has been characterized, BILL-Cadherin/cadherin-17 ( 47 ). Also, human pro-B cells express a pro-BCR ( 48 ).The other complex, as detected by the pre-BCR specific antibody SL156 was present on a small subpopulation of extremely large and cycling pre-B cells at the transition of pro-B and pre-B cells.…”
Section: Understanding the Function Of The Pre-b Cell Receptor In B Cmentioning
confidence: 99%
“…The λ5-UR is required for rapid internalization and signaling; in its absence mutant receptors with reduced signalling capacity accumulate on the surface ( 81 ). By contrast, the absence of the VpreB1-UR increases internalisation and hence was concluded to balance the rate of internalization ( 47 ). Moreover, pre-BCR surface levels are important as they seemingly regulate both proliferation and survival ( 82 ).…”
Section: Cell Autonomous Signaling And/or Ligand-mediated Signaling Bmentioning
confidence: 99%
“…Each SLC is composed of the l5 and VpreB proteins. The N terminus of l5 and the C terminus of VpreB contain unique regions (l5-UR and VpreB-UR, respectively) crucial for pre-BCR cell surface expression 24,25 and pre-BCR activation 18,24 . We recently found that GAL1 interacts with a l5-UR motif, l5-UR , of the pre-BCR that adopts a stable helical conformation that docks onto a GAL1 hydrophobic surface adjacent to the CBS 26 .…”
mentioning
confidence: 99%